Hukum Islam: Dasar, Sumber, Asas, Ruang Lingkup dan Tujuan Hukum - Anzalman, Anzalman; Thaheransyah; Kamal, Tamrin; SA, Saifullah; Asmaret, Desi; Julhadi, Julhadi (Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic law is a legal system designed to meet the spiritual and social needs of Muslims. In this study, we will discuss the basis, sources, principles, scope and objectives of Islamic law which functions as a guide to Muslim life. This study aims to understand the role of Islamic law in creating a balance between the interests of individuals and society and achieving social justice. The basis of Islamic law relies on the Al-Qur'an and Hadith as the main sources, complemented by secondary sources such as ijma' (consensus of ulama) and qiyas (analogies) to answer various new problems that are not explicitly regulated in the sacred text. The principles of Islamic law, including the principles of justice, benefit, equality before the law, and individual responsibility, provide the ethical foundation for the just application of the law. The scope of Islamic law includes aspects of worship, muamalah, family law, criminal law, and international law, all of which aim to create a harmonious and just society. Meanwhile, the aim of Islamic law or maqashid al-syari'ah emphasizes the protection of religion, soul, mind, lineage and property, which reflects the primary interest in realizing the welfare of the people. Through a comprehensive understanding, this study hopes to provide in-depth insight into the importance of Islamic law in the context of contemporary life and its role in sustainable moral and social development.